Management of Cryptocurrency Transactions from Accounting Aspects - Makurin, Andrii; Maliienko, Andrii; Tryfonova, Olena; Masina, Lyudmyla (Dr. Viktor Koval, 2023)
Introduction. An analysis of approaches to accounting for transactions with cryptocurrency states that the development of digital technologies and virtual markets has revealed a lack of readiness for the accounting display of such assets because there is no single approach to accounting for cryptocurrency transactions. Various regulatory documents have proposed considering cryptocurrency as an object that can be stocks, financial investments, monetary means, or intangible assets. Therefore, there is a need to determine exactly what cryptocurrency should be considered and which financial accounts should be displayed in the future. Aim and tasks. The purpose of the study is to identify the main characteristics of cryptocurrencies, which will help identify them as accounting objects. Based on this, it is necessary to study the main approaches to the display of such assets on financial accounts and to determine in which operations cryptocurrency can be used, and how to identify it. Results. It is established that the generation of cryptocurrency is affected by the approach of the miner, as he can generate new cryptocurrency, and all incurred costs are included in the cost price and form the initial value of the mined coin. However, if a miner can mine cryptocurrency using already existing technology, then the initial value must be capitalized on account 154 “Purchase (creation) of intangible assets” to form the initial value (cost). The identification criteria are as follows: receiving economic benefits, the sale operation will be completed, according to which cryptocurrency can be considered as reserves. The content of the operations (increase or decrease in exchange rate, formation of reports, etc.) for which cryptocurrency should be revalued on the relevant balance sheet date is given. Conclusions. Cryptocurrency can be considered a stock or an intangible asset. Modern blockchain technology affects accounting science by using triple rather than double recordings. This adds a level of entry, a cryptographic stamp with all transactions, and proves, however, that the interested parties (accountant, client, tax authorities, and auditor) will have an identical copy of the “ledger”. After achieving cryptocurrency price stability, such an asset can be used during international transactions, as it is more often used for speculative gains.